1974
DOI: 10.1063/1.1655396
|View full text |Cite
|
Sign up to set email alerts
|

Spatial dependence of the carrier lifetime in thin films of silicon on sapphire

Abstract: An experimental technique is described for determination of the generation carrier lifetime as a function of the distance of the insulator-semiconductor interface. This method is applied to thin films of silicon on sapphire nominally 1 μ thick and doped n type.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

1977
1977
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 9 publications
0
7
0
3
Order By: Relevance
“…This structure can be used to measure the carrier lifetime as a function of distance from the silicon-silicon dioxide surface. The lifetime was also shown by Schroder 63 and Kranzer 64 to decrease with increasing film doping concentration as evidenced in bulk silicon. 25.…”
Section: δν (Volts)mentioning
confidence: 62%
See 2 more Smart Citations
“…This structure can be used to measure the carrier lifetime as a function of distance from the silicon-silicon dioxide surface. The lifetime was also shown by Schroder 63 and Kranzer 64 to decrease with increasing film doping concentration as evidenced in bulk silicon. 25.…”
Section: δν (Volts)mentioning
confidence: 62%
“…Using this structure, Kranzer 64 showed that the carrier lifetime decreases monatonically with depth into the SOS film as shown in Fig. This structure can be used to measure the carrier lifetime as a function of distance from the silicon-silicon dioxide surface.…”
Section: δν (Volts)mentioning
confidence: 99%
See 1 more Smart Citation
“…The stress in SOS films was characterized by Raman spectroscopy [16], giving the values of 7.0±0.3 kbar at room temperature and 8.7±0.3 kbar at 77 K for films with thickness of 0.6Ͳ0.9 ʅm. The electrophysical properties of SOS films were studied as well [17], [18]. It was shown that the average carrier mobility and normalized impurity concentration are gradually decreasing functions of position within the film, with the maximum mobility observed on the film surface and the minimum mobility values found on the Si interface with the sapphire substrate.…”
Section: Introductionmentioning
confidence: 99%
“…The competition between film texture and stress is of great interest as both factors have a crucial effect on semiconductor electric properties. [13,14] Further characterization of charge-carrier lifetime and mobility properties of films should be carried out.…”
Section: Full Papermentioning
confidence: 99%